2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW) 2023
DOI: 10.1109/vrw58643.2023.00066
|View full text |Cite
|
Sign up to set email alerts
|

Can Gender and Motion Sickness Susceptibility Predict Cybersickness in VR ?

Abstract: VR headsets are becoming part of our everyday lives, however, cybersickness is a common side effect when using these devices. The experience and intensity of symptoms varies greatly between individuals with some seemingly resistant to cybersickness and other suffering greatly. It is still not clear why some individuals suffer more than others and what characteristics might contribute to such a resistance. In this study, we investigate two individual characteristics that have been commonly discussed in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In general, the motion sickness history, collected by the Motion Sickness Susceptibility Questionnaire (Golding 2006), is considered a good predictor for individual susceptibility to cybersickness as well (Jasper et al 2023). However, it solely considers the frequency of motion sickness occurring from physical movement, such as cars, airplanes, and amusement park rides and not from virtual environments and it shows inconsistent findings in predicting sickness as a result of VR exposure (Pöhlmann et al 2023). This may be important as there are generally some differences between susceptibility to cybersickness and motion sickness.…”
Section: Individual Differences In Susceptibility To Cybersicknessmentioning
confidence: 99%
“…In general, the motion sickness history, collected by the Motion Sickness Susceptibility Questionnaire (Golding 2006), is considered a good predictor for individual susceptibility to cybersickness as well (Jasper et al 2023). However, it solely considers the frequency of motion sickness occurring from physical movement, such as cars, airplanes, and amusement park rides and not from virtual environments and it shows inconsistent findings in predicting sickness as a result of VR exposure (Pöhlmann et al 2023). This may be important as there are generally some differences between susceptibility to cybersickness and motion sickness.…”
Section: Individual Differences In Susceptibility To Cybersicknessmentioning
confidence: 99%
“…However, a person's history of motion sickness was not associated with cybersickness symptoms. Accordingly, it was reported that the difference in the history of motion sickness between genders did not translate into cybersickness experiences as men and women experienced similar levels of cybersickness (Pöhlmann et al, 2023).…”
Section: Discussionmentioning
confidence: 99%